Sharia-Compliant Transformation of Village-Owned Enterprises: Accountability, Implementation, and Regulatory Readiness in West Nusa Tenggara - Asmawati, Asmawati; Fahrudin, Fahrudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the factors influencing the success of the transformation of Village-Owned Enterprises (BUMDes) into a sharia-compliant model in West Nusa Tenggara (NTB) province. Employing a Mixed Methods approach with a Sequential Exploratory design, this research integrates both qualitative and quantitative studies. The qualitative phase involved in-depth interviews with 7 key informants from BUMDes "Bareng Mele" to explore field challenges and practices. The findings indicate a strong commitment to sharia implementation but reveal obstacles such as communal accountability and a lack of a formal regulatory framework. The quantitative phase utilized a questionnaire distributed to 120 respondents to test the relationships between variables. The results of the multiple linear regression analysis show that Accountability, Implementation of Sharia Principles, and Regulatory Readiness have a significant simultaneous and partial effect on the Success of Sharia BUMDes Transformation. This study concludes that the success of the sharia BUMDes transformation requires a synergy between local commitment and structured regulatory support, as well as the formalization of accountability practices.